Long Noncoding Ribonucleic Acid SNHG18 Promotes Glioma Cell Motility via Disruption of α-Enolase Nucleocytoplasmic Transport - Zheng, Rong; Yao, Qiwei; Li, XiaoBo; Xu, Benhua (Frontiers in Genetics, 2019)
Glioma is a common malignancy with poor prognosis. Recent evidence suggests that the pathogenesis and progression of glioma involve long noncoding RNAs (lncRNAs). Previously, we showed that glioma cell radioresistance was enhanced by lncRNA SNHG18 in vitro and in vivo. In the present study, we showed that SNHG18 promoted the invasion and migration of glioma cells. SNHG18 was demonstrated to regulate the progression of epithelial-mesenchymal transition and cytoskeleton remodeling, thereby affecting cell motility. Furthermore, the promotion of invasion evoked by SNHG18 overexpression could be rescued by α-Enolase (ENO1) deletion. Moreover, rather than altering ENO1 expression, SNHG18 suppressed its nucleocytoplasmic transport by directly combining with ENO1 in glioma cells. The results suggested that SNHG18 inhibited the nucleocytoplasmic transport of ENO1 to promote cell motility. The results reveal the mechanism by which this lncRNA affects tumorigenesis and metastasis, forming the basis for further research that will lead to novel strategies to treat glioma.